PELAKSANAAN DESENTRALISASI PENDIDIKAN NASIONAL DAN IMPLIKASINYA TERHADAP PENGEMBANGAN PENDIDIKAN ISLAM - Rahim, Abdan (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2022)
Decentralization is the process of delegating or delegating power or authority from leaders or superiors to lower levels in the organization. The education management authority changed from a centralized system to a decentralized system. Decentralization of education means the transfer of power and broader authority to regions to make plans and make their own decisions in overcoming problems faced by education. This research is a type of library research (library research). Library research is research that is carried out starting from collecting data, information, and various other data taken from the library. It can be said that the implications of decentralization of education on Islamic education are not yet significant, because the development of Islamic education has not received special attention from the local government or city government so that it is not budgeted specifically in the APBD.